End-stage renal disease after renal cancer surgery: risk factors and overall survival - John Åkerlund; Börje Ljungberg; Sven Lundstam; Ralph Peeker; Erik Holmberg; Marianne Månsson; Anna Grenabo Bergdahl (Scandinavian Journal of Urology)
Objective: Several risk factors for end-stage renal disease (ESRD), in patients undergoing surgical treatment for renal cell carcinoma (RCC), have been suggested by others. This study aimed to investigate such risk factors and disclose the effect of developing ESRD, postoperatively, on overall survival. The risk of developing ESRD after RCC diagnosis was also evaluated.